2005
DOI: 10.1007/s00467-005-2101-8
|View full text |Cite
|
Sign up to set email alerts
|

Urinary aquaporin-2 in children with acute pyelonephritis

Abstract: Children with acute pyelonephritis develop polyuria and have reduced maximum urinary concentration capacity. We studied whether these abnormalities are associated with altered urinary excretion of the water channel aquaporin-2 (AQP2) in the renal collecting duct. AQP2 is the main target for antidiuretic action of arginine vasopressin (AVP), and the urinary excretion of this protein is believed to be an index of AVP signaling activity in the kidney. Children with acute pyelonephritis, aged 5-14 years, were exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…To date, no data have been published on renal excretion of aquaporin 2 in the urine, or the contribution of this protein to the regulation of water balance in neonatal farm animals. The only information on this subject comes from the studies on human and rat neonates (Tsukahara et al 1998a, b;Valenti et al 2000;Bonilla-Felix 2004;Radionova et al 2006;Iacobelli et al 2010;Li et al 2011). In this work, we report that expression of AQP2 in the urine of calves significantly increased in the first month of life after the administration of additional portion of lactose with milk replacer.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…To date, no data have been published on renal excretion of aquaporin 2 in the urine, or the contribution of this protein to the regulation of water balance in neonatal farm animals. The only information on this subject comes from the studies on human and rat neonates (Tsukahara et al 1998a, b;Valenti et al 2000;Bonilla-Felix 2004;Radionova et al 2006;Iacobelli et al 2010;Li et al 2011). In this work, we report that expression of AQP2 in the urine of calves significantly increased in the first month of life after the administration of additional portion of lactose with milk replacer.…”
Section: Discussionmentioning
confidence: 48%
“…In a study conducted in newborn rats it was shown that the reduced ability to retain water in the neonate kidney also results from low expression of AQP2 in the collecting ducts. The renal tubule expression of AQP2 and AQP2 excretion in neonates is about 50% lower than in adults (Yasui et al 1996;Tsukuhara et al 1998b;Radionova et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…AVP also stimulates the reabsorption of NaCl mediated by the epithelial sodium channel (ENaC) and activates the cAMP-sensitive cystic fibrosis transmembrane conductance regulator (CFTR) Cl − conductance in cultured renal collecting duct cells ( 11 13 ). Children with pyelonephritis exhibit increased levels of circulating AVP and develop polyuria with urinary concentrating defect, probably related to acute renal interstitial inflammation ( 14 16 ). However, this does not exclude that vasopressin may produce unexpected biological effects on renal cells independently of its antidiuretic action.…”
mentioning
confidence: 99%
“…Relative urinary AQP2 level in the samples was measured by dot immunoblotting as described previously [13]. Urine was applied on a nitrocellulose membrane using Bio-Dot microfiltration apparatus (Bio-Rad Laboratories, Sundbyberg, Sweden), and AQP2 was detected using rabbit polyclonal antibodies LL358 and ECL Plus Western blotting analysis system.…”
Section: Methodsmentioning
confidence: 99%